Childhood abuse and psychotic experiences – evidence for mediation by adulthood adverse life events. (9th October 2017) - Bhavsar, V.; Boydell, J.; McGuire, P.; Harris, V.; Hotopf, M.; Hatch, S. L.; MacCabe, J. H.; Morgan, C.
Abstract : Aims: We have previously reported an association between childhood abuse and psychotic experiences (PEs) in survey data from South East London. Childhood abuse is related to subsequent adulthood adversity, which could form one pathway to PEs. We aimed to investigate evidence of mediation of the association between childhood abuse and PEs by adverse life events. Methods: Data were analysed from the South East London Community Health Study (SELCoH, n = 1698). Estimates of the total effects on PEs of any physical or sexual abuse while growing up were partitioned into direct (i.e. unmediated) and indirect (total and specific) effects, mediated via violent and non-violent life events. Results: There was strong statistical evidence for direct (OR 1.58, 95% CI: 1.19–2.1) and indirect (OR 1.51, 95% CI: 1.32–1.72) effects of childhood abuse on PEs after adjustment for potential confounders, indicating partial mediation of this effect via violent and non-violent life events. An estimated 47% of the total effect of abuse on PEs was mediated via adulthood adverse life events, of which violent life events made up 33% and non-violent life events the remaining 14%. Conclusions: The association between childhood abuse and PEs is partly mediated through the experience of adverse life events in adulthood. There is some evidence that a larger proportion of this effect was mediated through violent life events than non-violent life events.